2008
DOI: 10.1177/1099800408320579
|View full text |Cite
|
Sign up to set email alerts
|

An Aerobic Weight-Loaded Pilot Exercise Intervention for Breast Cancer Survivors: Bone Remodeling and Body Composition Outcomes

Abstract: Objective Weight gain and bone loss are commonly reported in breast cancer survivors. The purpose of this pilot study is to assess feasibility and explore the effect of an aerobic weight-loaded exercise intervention on bone remodeling, weight, and body composition. Design A one-group pre-posttest design was used to test a 16–24-week supervised walking exercise intervention among women within 2 years of menopause. Through Weeks 1–4, time and weight were progressively increased. By Week 5 and through the end o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 52 publications
1
54
0
Order By: Relevance
“…1). Of the 36 full papers reviewed, 25 were excluded because no bone outcome was included in the trial, leaving 11 papers that met our inclusion criteria [23][24][25][26][27][28][29][30][31][32][33]. Two trials that reported BMD assessment in the methods were excluded because BMD results were not reported [32,33].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). Of the 36 full papers reviewed, 25 were excluded because no bone outcome was included in the trial, leaving 11 papers that met our inclusion criteria [23][24][25][26][27][28][29][30][31][32][33]. Two trials that reported BMD assessment in the methods were excluded because BMD results were not reported [32,33].…”
Section: Resultsmentioning
confidence: 99%
“…Three of the controlled trials compared an exercise group to a usual care comparison group [25,26,29] and two had pharmacologic comparison groups with one comparing exercise versus drug therapy [28] and one comparing drug therapy alone to drug therapy plus exercise [31]. Three studies reported bone health as the only primary endpoint [28,29,31], three included bone health as a primary endpoint along with body composition (lean and fat mass) [24,25] and physical function [23]. One measured BMD among several outcomes, but did not report which outcome was their primary endpoint [30] and a behavioral intervention aimed to increase physical activity included BMD as a secondary endpoint [26].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 70 controlled trials have examined exercise in breast cancer patients and survivors; however, only seven have examined bone health outcomes [71][72][73][74][75][76][77]. Studies assessing bone health in breast cancer patients have typically included women who are peri-or postmenopausal [71][72][73][74][75][76]78], are at least 6 months post primary chemotherapy or radiation therapy [71,72,[75][76][77] and receiving adjuvant selective estrogen receptor modulators or aromatase inhibitors [71][72][73][74][75][76][77].…”
Section: Exercise and Cancer-related Bone Loss In Women With Breast Cmentioning
confidence: 99%
“…In a pre-post-test design, Knobf and colleagues assessed the effects of a 16 to 24 week, weight-loaded aerobic exercise intervention for 26 Stage I and II pre-or perimenopausal breast cancer patients who had completed chemotherapy and/or radiation therapy (27% of whom were also undergoing adjuvant hormonal therapy with tamoxifen or aromatase inhibitors) [72]. The supervised, communitybased intervention consisted of treadmill walking while wearing a weight belt and weighted backpack, three times per week.…”
Section: Exercise and Cancer-related Bone Loss In Women With Breast Cmentioning
confidence: 99%